A Dalliance with Dailyatia:significant new information on an enigmatic lophotrochozoan animal from the lower Cambrian of Australia and Antarctica - Brock, Glenn A.; Skovsted, Christian B.; Topper, Timothy P.; Betts, Marissa J. (2012)
Dailyatia is an enigmatic tommotiid genus endemic to lower Cambrian successions of East Gondwana (Australia and Antarctica). The plethora of sclerite mor photype variation has made the taxonomy of the genus highly problematic. Recovery of 6750 Dailyatia sclerites from more than 20 separate measured stratigraphic sections and 100+ spot localities from the Flinders Ranges (Arrowie Basin) of South Australia reveals hither to unappreciated species-level diversity. Superbly preserved new material provides intriguing new morphological and ultrastructural data -- including the presence of bizzare honeycomb-like apicies and a possible partial scleritome fragment. An elongate, tapering tube attached to the inner surface of a few, rare sclerites appears to match sclerite growth but extends well beyond the margin of the sclerite. This possible pathological response to parasitism or internal shell damage reveals important new information about sclerite growth and functional morphology. Detailed investigation indicates that all 5 species of Dailyatia have discreet, and in some cases, mutually exclusive stratigraphic ranges -- potentially important for regional biostratigraphic subdivision of Hawker Group rocks in the Arrowie Basin. The new palaeobiological and biostratigraphic information about Dailyatia (and other camenellans) will help decipher the complex timing of character assembly and morphological transformations from a deep root within the lophotrochozoan phylogenetic tree.